FACE THREATENING ACT ON MAIN CHARACTER’S UTTERANCES OF 300 MOVIE - UTOMO, NOVIAN DWI CAHYO (Jurnal Ilmiah Mahasiswa FIB, 2013)
People need to convey certain messages which are delivered to the addressee as a form of cooperation when having communication with others as social beings. In producing utterance in communication, people often perform face threatening acts (FTAs) which cause damages to the hearer’s face. The writer conducted a study about FTA in 300 movie which presents about politeness phenomena happening in life aspect at the ancient time of Greece. There are two problems to be solved, they are: (1) What utterances containing Face-Threatening Acts are found on main character’s utterances of 300 movie and (2) What FTA strategies are used by the main character’s utterances of 300 movie.This study uses qualitative approach to gather and analyze the data. It is included into document analysis in analyzing and interpreting the utterances produced by the main character of 300 movie through the script of the movie.The results of this study shows that there are four FTA strategies applied by main character of the movie, they are: Bald on-record, positive politeness, negative politeness, and indirect strategy. King Leonidas uses those strategies to perform FTAs. In the appliance of FTA strategies, he mostly used positive politeness in his utterance to show cooperation and effort to minimize the social distance with others. However, he still considers to perform FTA baldly in giving orders to his soldiers.Based on the results, the writer suggests to the next researchers to use other objects reflecting more about performing FTA in daily life also use more theories in analyzing the implicit meanings of the speaker’s utterances. Keywords: Politeness, Face, Face Threatening Act (FTA).